Local level Politics ; Social and Cultural Perspectives / edited by Marc J. Swartz - "Swartz, Marc J. (ed.)" (London, 1969)
Viewing political activity as a dynamic process rather than as the operation of immutable structures, the writers who have contributed to this book study the politics of small communities in different parts of the world.
Keywords: Political science